Biochemical Characterization of a New Oligoalginate Lyase and Its Biotechnological Application in Laminaria japonica Degradation - Li, Shangyong; Wang, Linna; Jung, Samil; Lee, Beom Suk; He, Ningning; Lee, Myeong-Sok (Frontiers in Microbiology, 2020)
Oligoalginate lyases belong to family 17 of polysaccharide lyases (PL) that preferred β-D-mannuronic acid (M) into monomeric sugar, providing feedstock for biofuels. The M-preferred substrate recognition and binding mechanism of this family has not been fully elucidated. In this study, we report the cloning, expression and biochemical characterization of a new PL17 oligoalginate lyase, OalV17, from the marine bacterium Vibrio sp. SY01. The recombinant OalV17 showed metal ion independent and detergent resistant properties. Furthermore, OalV17 is an exo-type enzyme that yields alginate monomers as the main product and recognizes alginate disaccharides as the minimal substrate. Site-directed mutagenesis followed by kinetic analysis indicates that the residue Arg231 plays a key role in substrate specificity. Furthermore, a rapid and efficient alginate monomer-producing method was developed directly from Laminaria japonica. These results suggest that OalV17 is a potential candidate for saccharification of alginate.